The position of liquid fuel residues in tank of worked-off rocket stage during ballistic descent - V. Yu. Kudentsov; A. V. Kudentsov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The results of modeling the behavior of liquid residues of the rocket fuel component in the fuel tank of the worked-off rocket stage on a ballistic trajectory are presented. The simulation is carried out for the following variants: during the controlled descent of the rocket stage and when using the technology of evaporation of liquid rocket fuel residues in the tanks of the spent stage. It is established that during the controlled descent of the spent rocket stage along the ballistic trajectory at the site of its turn and up to heights of 20 km, the liquid under the influence of overloads is distributed in the form of a film in the area of the bottom and side surface with a coverage area of up to 35 %. At the height of the maximum value of the axial overload, liquid fuel residues in the form of a film move to the area of the bottom and the adjacent side surface of the fuel tank. The total coverage area is about 22 %. The introduction of a hot coolant into the fuel tanks to vaporize the liquid remnants of rocket fuel radically changes the picture of the behavior of the liquid. Due to the high speed of the coolant in the tank, axial overload has little effect on the distribution of fuel residues in the rocket tank